Experimental study on water migration in unsaturated loess under an electric field: optimization of electrode material - Jiao, Dan; He, Zhiheng; Wang, Tiehang; Zhang, Yonggang (Frontiers in Earth Science, 2025)
Electroosmosis method is an environmentally friendly and low-carbon foundation treatment technique that can quickly improve soil shear strength. To investigate the effect of electric potential on water migration in unsaturated loess, this study employed a custom-designed one-dimensional laboratory experimental device to conduct electroosmosis experiments with six different electrode materials: copper, aluminum, stainless steel, nickel, graphite, and iron. Changes in water content within the unsaturated loess were monitored before and after the experiments. The internal current, electric potential distribution, interface resistance, and soil resistivity were observed during the experiments. The results indicated that: (1) the maximum and minimum water migration amounts were 8% and 3.4%, respectively, with the maximum being 2.35 times the minimum. The preferred ranking of electrode materials for soil water migration efficiency was stainless steel > nickel > graphite > aluminum > copper > iron. (2) The effective electric potential of soil samples across all six test soil samples continuously decreased with increasing electrification duration, while the current initially increased and then decreased. The interface resistance continuously increased, while the soil resistivity for graphite electrode rapidly increased over time. Based on the variations in various parameters and energy efficiency during the experiments, the optimal ranking of electrode materials was as follows: graphite > stainless steel > nickel > aluminum > copper > iron; (3) Due to their high energy utilization rates and strong corrosion resistance, stainless steel, nickel, and graphite are recommended as the preferred electrode materials for both laboratory and field tests. In practical engineering applications, moisture migration volume is prioritized; thus, the final electrode selection order is: stainless steel > nickel > graphite > aluminum > copper > iron.